2014
DOI: 10.1186/1471-2474-15-212
|View full text |Cite
|
Sign up to set email alerts
|

The spinal posture of computing adolescents in a real-life setting

Abstract: BackgroundIt is assumed that good postural alignment is associated with the less likelihood of musculoskeletal pain symptoms. Encouraging good sitting postures have not reported consequent musculoskeletal pain reduction in school-based populations, possibly due to a lack of clear understanding of good posture. Therefore this paper describes the variability of postural angles in a cohort of asymptomatic high-school students whilst working on desk-top computers in a school computer classroom and to report on the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0
4

Year Published

2015
2015
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(17 citation statements)
references
References 34 publications
1
12
0
4
Order By: Relevance
“…Reasons for this discrepancy between the predictors of pain presence and predictors of pain intensity are outside the scope of this work. Nevertheless, several reasons may explain the association between time spent in screen based activities and pain intensity: i) the flexed and end of range postures that students tend to use during screen based activities [ 33 , 34 ] may place excessive strain and/or stretch on sensitive structures; the long periods of time spent in static positions may further contribute to increase strain while also decreasing the appropriate oxygenation and removal of metabolites and algic substances from tissues, increasing nociceptive activity. There is some evidence in support of the proposed hypothesis: a prospective study on the association between posture during desk top computer use and pain found that increased head flexion predicted pain of higher intensity even when adjusted for psychosocial factors [ 35 ]; 1 h of combined workstation tasks resulted in decreased oxygen saturation and blood flow in all three parts of the trapezius muscle and 90 min of computer based work significantly increase pain intensity [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…Reasons for this discrepancy between the predictors of pain presence and predictors of pain intensity are outside the scope of this work. Nevertheless, several reasons may explain the association between time spent in screen based activities and pain intensity: i) the flexed and end of range postures that students tend to use during screen based activities [ 33 , 34 ] may place excessive strain and/or stretch on sensitive structures; the long periods of time spent in static positions may further contribute to increase strain while also decreasing the appropriate oxygenation and removal of metabolites and algic substances from tissues, increasing nociceptive activity. There is some evidence in support of the proposed hypothesis: a prospective study on the association between posture during desk top computer use and pain found that increased head flexion predicted pain of higher intensity even when adjusted for psychosocial factors [ 35 ]; 1 h of combined workstation tasks resulted in decreased oxygen saturation and blood flow in all three parts of the trapezius muscle and 90 min of computer based work significantly increase pain intensity [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…It has been indicated that this posture might contribute to the onset and perpetuation of neck and back pain syndromes, with further loss of cervical spine extension (Burgess‐Limerick, Plooy & Ankrum, ; McEvoy & Grimmer, ). Forward head posture is determined by a dynamic combination of daily life factors, such as computer use (Brink, Louw, Grimmer & Jordaan, ). Incorrect posture of the head and neck has been correlated with chronic musculoskeletal pain (Lau, Cheung, Chan, Lo & Chiu, ; Szeto, Straker & Raine, ).…”
Section: Introductionmentioning
confidence: 99%
“…Work-related hand disorders like carpal tunnel syndrome and pain in the forearm and wrist may be found in computer users as well [ 1 , 22 ]. Many of these conditions develop due to an insufficient quantity of body movements and due to the permanent muscular contraction required for maintaining a stable posture for a prolonged time period [ 1 , 23 , 24 ]. Such inactivity results in the decline of microcirculation in the extremities and organs, impaired oxygenation of tissues, and disturbed elimination of metabolic waste products [ 1 , 25 , 26 , 27 , 28 , 29 ].…”
Section: Introductionmentioning
confidence: 99%